A multi-omics study to characterize the transdifferentiation of human dermal fibroblasts to osteoblast-like cells - Pihlström, Sandra; Määttä, Kirsi; Öhman, Tiina; Mäkitie, Riikka E.; Aronen, Mira; Varjosalo, Markku; Mäkitie, Outi; Pekkinen, Minna (Frontiers in Molecular Biosciences, 2022)
Background: Various skeletal disorders display defects in osteoblast development and function. An in vitro model can help to understand underlying disease mechanisms. Currently, access to appropriate starting material for in vitro osteoblastic studies is limited. Native osteoblasts and their progenitors, the bone marrow mesenchymal stem cells (MSCs), are problematic to isolate from affected patients and challenging to expand in vitro. Human dermal fibroblasts are a promising substitute source of cells. Method: We developed an in vitro culturing technique to transdifferentiate fibroblasts into osteoblast-like cells. We obtained human fibroblasts from forearm skin biopsy and differentiated them into osteoblast-like cells with β-glycerophosphate, ascorbic acid, and dexamethasone treatment. Osteoblastic phenotype was confirmed by staining for alkaline phosphatase (ALP), calcium and phosphate deposits (Alizarin Red, Von Kossa) and by a multi-omics approach (transcriptomic, proteomic, and phosphoproteomic analyses). Results: After 14 days of treatment, both fibroblasts and MSCs (reference cells) stained positive for ALP together with a significant increase in bone specific ALP (p=0.04 and 0.004, respectively) compared to untreated cells. At a later time point, both cell types deposited minerals, indicating mineralization. In addition, fibroblasts and MSCs showed elevated expression of several osteogenic genes (e.g. ALPL, RUNX2, BMPs and SMADs) and decreased expression of SOX9. Ingenuity Pathways Analysis of RNA sequencing data from fibroblasts and MSCs showed that the osteoarthritis pathway was activated in both cell types (p_adj.=0.003 and 0.004, respectively). Discussion: These data indicate that our in vitro treatment induces osteoblast-like differentiation in fibroblasts and MSCs, producing an in vitro osteoblastic cell system. This culturing system provides an alternative tool for bone biology research and skeletal tissue engineering.